Chronic rejection in vascularized composite allotransplantation. Issue 5 (October 2018) - Morelon, Emmanuel; Petruzzo, Palmina; Kanitakis, Jean
Abstract : Purpose of review: Vascularized composite allografts (VCA), which restore severely damaged body parts that cannot be repaired with conventional surgical techniques, often undergo acute skin rejection episodes in the early postgraft period. Although the risk of human VCA to be affected by chronic rejection was initially unknown, such cases were recently observed. Recent findings: Chronic rejection targets preferentially the skin (dermal sclerosis, adnexal atrophy, necrosis) and vessels (graft vasculopathy) and may cause graft dysfunction, often resulting in ischemic graft loss. Both immune (cell-mediated and antibody-mediated) and nonimmune mechanisms seem to be involved. The early diagnosis and management of chronic rejection are challenging. Changes of chronic rejection may be seen macroscopically on the skin and can be confirmed with skin and deep tissue biopsies. New noninvasive imaging techniques, which allow visualization of the allograft vasculature, seem promising for the noninvasive detection of graft vasculopathy. Summary: Although some features of chronic rejection of VCA start to be known, several important questions remain to be answered, concerning namely the proper definition of chronic rejection, precise diagnostic criteria, better understanding of triggering factors and pathogenetic mechanisms involved and, most importantly, adequate treatment. Ideally, chronic rejection should be prevented in the future by efficient tolerance-inducing protocols.